CFD simulation, change of wind velocity through netting as perforated barrier (2019)
Main purpose of this article is determining the change in wind velocity and direction around and through the aerodynamic barrier. The barriers are made of four different types permeable materials and one barrier made of impermeable material. In the article is detailed description of the simulation procedure of the precise barriers in the program (CFD) Ansys Fluent 19.2. The simulation of the particular barriers consists of determining the eligible size of the computational domain, which proposition was based on the connections with the barrier height, since the barrier width is negligible in this case. Choosing the suitable computational model for the simulation was important, especially being based on the Reynolds Averaged Navier-Stokes equations. Based on the Forschheimer's equation, eligible positioning location of the aerodynamic barrier and adjustment for the permeability of individual materials in computer simulations. Conclusion of this article is the evaluation of the aerodynamic barrier simulations with simple pointing at the speed changes and wind flow, around and through the aerodynamic barriers.